SARS-CoV-2 Infection in Asymptomatic Patients Hospitalized for Cardiac Emergencies: Implications for Patient Management - Kessler, Thorsten; Wiebe, Jens; Graf, Tobias; Schunkert, Heribert; Kastrati, Adnan; Sager, Hendrik B. (Frontiers in Cardiovascular Medicine, 2020)
Background: The coronavirus disease (COVID-19) pandemic imposed diverse challenges on the health care system. Morbidity and mortality of non-COVID-19 emergencies might also have changed because hospitals may not be able to provide optimal care due to restructured resources and uncertainties how to deal with potentially infected patients. It has been recommended to stratify treatment of cardiovascular emergencies according to cardiovascular risk. However, data on the prevalence of asymptomatic SARS-CoV-2 infection in patients presenting with cardiac emergencies remain scarce. Methods: We retrospectively analyzed patients’ data from a tertiary cardiology department between April 15 and May 31, 2020. All patients were screened on admission for COVID-19 symptoms using a questionnaire and body temperature measurements. All hospitalized patients were routinely screened using nasopharyngeal swab testing. Results: In total, we counted 710 urgent and emergency admissions. Nasopharyngeal swab tests were available in 689 (97%) patients, 409 and 280 of which presented as urgent and emergency admissions, respectively. Among 280 emergency admissions, none tested positive for SARS-CoV-2. Conclusion: In cardiac emergency patients which were screened negative for COVID-19 symptoms, the prevalence of SARS-CoV-2 infection in regions with a modest overall prevalence is low. This finding might be helpful to better determine timing of emergency procedures and reasonable usage of protective equipment during the COVID-19 crisis and the future.